PROPERTIES OF PROTEINASE FROM STREPTOCOCCUS FAECALIS VAR. LIQUEFACIENS - Bleiweis, Arnold S. (1964)
Bleiweis, Arnold S. (The Pennsylvania State University, University Park), and Leonard N. Zimmerman. Properties of proteinase from Streptococcus faecalis var. liquefaciens. J. Bacteriol. 88:653–659. 1964.—The extracellular group D streptococcal proteinase is inactivated by chelating agents [ethylenediamine-tetraacetate (EDTA), o-phenanthroline, and 8-quinolinol] and mercaptans (cysteine, mercaptoethanol, and thioglycolate). The optimal inhibitory concentrations of EDTA (4 × 10(−4)m) and cysteine (2.5 × 10(−2)m) promote rapid loss of activity with 50% inactivation after 4 to 5 min. Enzyme inactivated by either EDTA or cysteine is reactivated about 80% by 4 × 10(−4)m Zn(++). Such reactivation of EDTA-treated enzyme is prevented completely by iodoacetate (5 × 10(−2)m) and of cysteine-treated enzyme by oxidizing conditions, which suggests that the zinc binding-site may be a thiol. High levels of zinc (10(−3)m) do not allow reactivation in either case, and actually inhibit native proteinase. Ca(++), Mg(++), Co(++), Fe(++), Cu(++), and Ni(++) do not reactivate cysteine-treated enzyme, but Mn(++) (10(−4) to 8 × 10(−4)m) allows 27% reversal. N(2)-held, cysteine-treated enzyme can be spontaneously reactivated if the substrate is flushed with O(2) during the assay; leakage of air or O(2) into the samples before assay leads to loss of reactivatability. Native proteinase does not lose activity after dialysis for 43 hr against 0.07 m phosphate buffer. It is concluded that the group D proteinase obtained from Streptococcus faecalis var. liquefaciens is probably a zinc metalloenzyme that is unlike the thiol-activated, group A streptococcal proteinase, but similar to the mammalian carboxypeptidase A.